2010
DOI: 10.21608/ejchem.2010.1268
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Thermal Decomposition of Iron Carbonate

Abstract: HE THERMAL decomposition of iron cabonate in air was ……studied by means of DTA-TG, XRD, SEM and Mossbauer measurements. The kinetics of the thermal decomposition process were studied using isothermal and non-isothermal thermogravimetric techniques. The results show that the thermal decomposition proceeds in one step to iron oxide. Kinetic analysis of isothermal data of the decomposition reaction in the light of various solid state reaction models revealed that the reaction is best described by the diffusion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This can be observed in the figure where the largest peak (third peak) was noticeable, which indicates that this temperature interval is important because this is where the thermal decomposition of carbonate products (i.e., FeCO 3 and CaCO 3 ) occurred. This observation is in agreement with the study by El-Bellihi [53], where it has been stated that the decomposition of iron carbonate resulted in a peak at 495 • C. Stopic et al [48] also discussed the thermal decomposition of their sample and identified that a temperature interval of 470-595 • C was associated with magnesium/iron carbonate decomposition. Furthermore, Mendoza et al [47] mentioned that at 367 • C, siderite (FeCO 3 ) begins to decompose and release carbon dioxide.…”
Section: Influence Of Particle Size Fraction On Uptake Capacitysupporting
confidence: 88%
See 2 more Smart Citations
“…This can be observed in the figure where the largest peak (third peak) was noticeable, which indicates that this temperature interval is important because this is where the thermal decomposition of carbonate products (i.e., FeCO 3 and CaCO 3 ) occurred. This observation is in agreement with the study by El-Bellihi [53], where it has been stated that the decomposition of iron carbonate resulted in a peak at 495 • C. Stopic et al [48] also discussed the thermal decomposition of their sample and identified that a temperature interval of 470-595 • C was associated with magnesium/iron carbonate decomposition. Furthermore, Mendoza et al [47] mentioned that at 367 • C, siderite (FeCO 3 ) begins to decompose and release carbon dioxide.…”
Section: Influence Of Particle Size Fraction On Uptake Capacitysupporting
confidence: 88%
“…Following this peak, all samples started to exhibit different peaks starting from 340 • C. At the temperature interval of 340-660 • C, the raw and carbonated samples of pH N shows a strong peak with a high weight loss disparity of 3.72% and 8.04%, respectively. On the other hand, peaks observed for pH 8-12 were at temperatures of 340-630 • C and were closely followed by another peak at around 630-700 • C. According to El-Bellihi [53] and Stopic et al [48], this can be attributed to the thermal decomposition of carbonate product, which can be seen in the temperature interval around 340-660 • C for pH N with a weight reduction of 8.04% and 340-630 • C for pH 8-12 with a weight reduction of 6.84%, 6.43% and 6.84%, respectively. A small peak around temperatures of 630-700 • C in pH 8-12 can be ascribed to the reduction of ferric oxide (Fe 2 O 3 ) or residuals from iron carbonate thermal decomposition into magnetite (Fe 3 O 4 ) [47,51].…”
Section: Carbonation Process Optimization: Effect Of Different Parame...mentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, FeO is often described as an intermediate product toward the transformation to Fe 3 O 4 in CO 2 environments, and therefore, it is likely that the order of formation of these corrosion products has been FeCO 3 → FeO → Fe 3 O 4 . It is worth noting that, if oxygen is present, FeO rapidly transforms to Fe 2 O 3 . …”
Section: Resultsmentioning
confidence: 99%
“…However, the analyzed slags contain only up to 2.47% CaO, proving that no calcite was added as a flux. Moreover, during smelting, carbonates in the charge decompose at temperatures well below the liquidus temperature of the analyzed slags [38,39]. Isotope analyses of charcoal are also subject to errors related to the old wood effect [36].…”
Section: Agementioning
confidence: 99%